Microscopic emphysema in relation to age and smoking habit. - Gillooly, M (1993)
BACKGROUND--The increases in airspace size within the human lung associated with microscopic emphysema can be assessed by measuring the airspace wall surface area per unit volume of lung tissue (AWUV). In a previous study the limits of normality of AWUV with age were estimated in lifelong non-smokers by the 95% prediction limits of the regression line for these variables. The aims of this study were to study the incidence of microscopically assessed emphysema in a group of smokers and to examine the influence of smoking habit on the susceptibility to and severity of microscopically assessed emphysema. METHODS--AWUV was measured on tissue sections from 125 lung specimens obtained from tobacco smokers (mean age 61.1 (range 33-85) years) with the fast interval processor, a rapid automatic scanning device. The mean AWUV value was calculated for each specimen and this figure was plotted against the age of the subject. The limits of normal AWUV were plotted, and AWUV values below these limits were taken as indicative of microscopically assessed emphysema. Details of the number of cigarettes smoked each day were obtained for 97 of the smokers. These subjects were grouped according to smoking habit: group 1, 1-19 cigarettes/day; group 2, 20-29 cigarettes/day; group 3, at least 30 cigarettes/day. The AWUV results from each of these groups were then assessed. RESULTS--Mean AWUV decreased with age in this group of smokers, but only 26% had microscopically assessed emphysema, indicating that within the group there were two subgroups of smokers with differing susceptibility to microscopically assessed emphysema. There were no sex differences in the incidence of microscopically assessed emphysema, nor were the incidence and severity increased with increased daily cigarette consumption. CONCLUSIONS--Susceptibility to microscopically assessed emphysema was found to be similar in male and female smokers. Daily cigarette consumption did not appear to be the primary factor influencing the susceptibility to or severity of microscopically assessed emphysema. Susceptibility differences within the smoking population should be taken into consideration in studies of the pathogenesis of emphysema.